Lama Waktu Tunggu Konsumsi Menurunkan Kandungan Vitamin C Pada Jus Campuran Pepino-Belimbing - Ayangsari Cahyaningrum; Sri Winarsih; Yudi Arimba Wani (Universitas Muhammadiyah Semarang, 2017)
Pepino is a fruit that has been widely cultivated in Indonesia. Pepino contains high antioxidants that one of them is vitamin C. Vitamin C can improve endothelial vasodilation and has antihypertensive effect. To improve the taste of pepino need to be mixed with starfruit. Starfruit has been selected because it proved capability of lowering blood pressure. This study aims to determine differences in the content of vitamin C in the juice mixture of pepino and starfruit on juicing and blending processing methods, as well asdifferences in the content of vitamin C in a holding time of 5, 20, 35, 50, and 65 minutes in each of the processing method. This study was an experimental study with completely randomized factorial design. The mixed juice of pepino and starfruit used in this study was pepino (70%):starfruit (30%). Level of treatment used were juicing and blending. Analysis vitamin C using iodometric titration method. The results showed vitamin C (mg/L) in a mixture of pepino and starfruit juice with juicing processing methods on the holding time 5, 20, 35, 50, and 65 minutes respectivelywere 911.7; 863.73; 840.9; 813.6; and 791.5. While, in the processing method of blendingwere 864.1; 528.7; 478; 421.23; and 387.97. The conclusion of this study was no significant difference between the vitamin C content processing method of juicing by blending the holding time of 5 to 65 minutes. As well as a decrease in vitamin C on the processing method of juicing and blending began holding time of 5 to 65 minutes. However, it was not significant in the juicing method (3.45% every 15 minutes) and significant at the blending method (13.03% every 15 minutes). Keywords : vitamin C, pepino, starfruit, juicing, blending, holding time